The Effect of Fermentation Time on the Chemical and Sensory Characteristics of Yoghurt Containing Eucheuma cottonii Seaweed - Deden Yusman Maulid; Nusaibah Nusaibah; Arpan Nasri Siregar; Muhamad Hikam Idris; Endah Yuniarti (Universitas Islam Raden Rahmat, Malang, 2025)
Eucheuma cottonii is a seaweed from the Rhodophyta group (red algae) which is widely used in the food industry, especially carrageenan. The fiber content in seaweed comes from cellulose and hemicellulose, carrageenan, agar, and alginate. Yogurt has an important role in the body, such as maintaining stomach health, preventing cancer, and improving the digestive tract. This study aims to determine the effect of fermentation time on the chemical and sensory characteristics of yogurt added with Eucheuma cottonii seaweed. The long fermentation treatment used consisted of P1 = 12 hours; P2= 14 hours; and P3 = 16 hours. The addition of E. Cottonii seaweed to yogurt with a 12-hour fermentation time showed the highest parameters by SNI yogurt compared to other treatments. These parameters consist of moisture content, fat content, and ash content. The fermentation time of 16 hours in yogurt containing E. Cottonii seaweed showed the highest effect on sensory characteristics compared to other treatments. Based on this, yogurt fermentation time can determine the chemical and sensory characteristics of the product.